Imprintability of Newly Hatched Domestic Chicks on an Artificial Object: A Novel High Time-Resolution Apparatus Based on a Running Disc - Aoki, Naoya; Mori, Chihiro; Fujita, Toshiyuki; Serizawa, Shouta; Yamaguchi, Shinji; Matsushima, Toshiya; Homma, Koichi J. (Frontiers in Physiology, 2022)
In filial imprinting, newly hatched chicks repeatedly approach a conspicuous object nearby and memorize it, even though it is an artificial object instead of their mother hen. Imprinting on an artificial object in a laboratory setting has a clear sensitive period from post hatch days 1 to 3 in the case of domestic chicks. However, the establishment of imprintability are difficult to investigate because of the limitations of the behavioral apparatus. In this study, we developed a novel behavioral apparatus, based on a running disc, to investigate the learning processes of imprinting in newly hatched domestic chicks. In the apparatus, the chick repeatedly approaches the imprinting object on the disc. The apparatus sends a transistor-transistor-logic signal every 1/10 turn of the disc to a personal computer through a data acquisition system following the chick’s approach to the imprinting object on the monitor. The imprinting training and tests were designed to define the three learning processes in imprinting. The first process is the one in which chicks spontaneously approach the moving object. The second is an acquired process in which chicks approach an object even when it is static. In the third process, chicks discriminate between the differently colored imprinting object and the control object in the preference test. Using the apparatus, the difference in the chicks’ behavior during or after the sensitive period was examined. During the sensitive period, the chicks at post hatch hour 12 and 18 developed the first imprinting training process. The chicks at post hatch hour 24 maintained learning until the second process. The chicks at post hatch hour 30 reached the discrimination process in the test. After the sensitive period, the chicks reared in darkness until post hatch day 4 exhibited poor first learning process in the training. Thus, this apparatus will be useful for the detection of behavioral changes during neuronal development and learning processes.